Dissimilar joining of AZ31B magnesium alloy and pure copper via thermo-compensated resistance spot welding. (December 2017) - Shan, He; Zhang, Yu; Li, Yang; Luo, Zhen
Graphical abstract: Abstract: The feasibility of Mg/Cu dissimilar resistance spot welding (RSW) was investigated via a thermo-compensated process. Both physical factors and metallurgical properties of the welds affected the tensile shear properties of the joints. The mechanical properties of the Mg/Cu RSW joints were determined by the competitive relationship between these two factors. The increase in the nugget size with increasing Joule heat input improved the load-bearing ability of the joints. However, at the same time, the microstructure of the nugget transformed from an α-Mg solid solution fusion zone with a thin transition layer into an intermetallic compound (IMC)-enriching fusion zone with a thick transition layer. The mechanical properties of the joints deteriorated, owing to this transformation. All the Mg/Cu RSW samples fractured via interfacial failure (IF) mode and exhibited cleavage features. Although their ductility deteriorated owing to the IMCs, the Mg/Cu thermo-compensated RSW joints exhibited satisfactory tensile shear peak loads (maximum: 2626 N), which are comparable to that (2745 N) of Mg/Mg RSW joints. A reliable welding lobe suitable for industrial manufacture was obtained, when a welding time and a welding current of 100 ms–400 ms and 12 kA–20 kA, respectively, were recommended.